KOLABORASI KULTUR DAN KONSEP AL-‘URF DALAM MEMBANGUN FIKIH MAZHAB INDONESIA - Saifudin Zuhri (Jurnal Dialog, 2015)
The Indonesian fiqh schools in Indonesia become unique as it relies on the national cultures as the colors of fiqh. Diverse cultural factors and the vast number of Muslim population around 80% out of 235 millions of the population account for the Indonesian fiqh to be considered among the Islamic fiqh schools. Some fiqh innovations were produced due to legal collaboration between fiqh legal and Indonesian culture. The development of fiqh schools has been clearly demonstrated in the Sabilul Muhtadin book, a work of Muhammad Arsyad al-Banjari (1710-1812 AD), which continues today in the hands of Gus Dur, Ali Yafie, and others. Harmonious collaboration between Indonesian customs and Islam becomes a positive and progressive synergy in developing.